Low-background neutron activation analysis: a powerful tool for atmospheric mineral dust analysis in ice cores - Baccolo G.; Maffezzoli N.; Clemenza M.; Delmonte B.; Prata M.; Salvini A.; Maggi V.; Previtali E. (Journal of Radioanalytical and Nuclear Chemistry, 2015)
The application of instrumental neutron activation analysis (INAA) for multi-elemental analysis of samples of extremely reduced mass such as dust samples extracted from ice cores requires specific efforts towards the development of a “low level counting” analytical technique. An analytical protocol specifically designed for this kind of samples, based on low-background INAA (LBNAA) is here presented. A first application of the method was successfully performed on samples from the new alpine firn core NextData-LYS12. Sub-ng detection limits were reached for many elements. According to this point the technique is also potentially suitable to be applied to polar ice core samples.